Centrosome – a promising anti-cancer target - Rivera-Rivera Y (Dove Medical Press, 2016)
Yainyrette Rivera-Rivera, Harold I Saavedra Department of Pharmacology, Ponce Health Sciences University-School of Medicine, Ponce Research Institute, Ponce, Puerto Rico Abstract: The centrosome, an organelle discovered >100 years ago, is the main microtubule-organizing center in mammalian organisms. The centrosome is composed of a pair of centrioles surrounded by the pericentriolar material (PMC) and plays a major role in the regulation of cell cycle transitions (G1-S, G2-M, and metaphase-anaphase), ensuring the normality of cell division. Hundreds of proteins found in the centrosome exert a variety of roles, including microtubule dynamics, nucleation, and kinetochore–microtubule attachments that allow correct chromosome alignment and segregation. Errors in these processes lead to structural (shape, size, number, position, and composition), functional (abnormal microtubule nucleation and disorganized spindles), and numerical (centrosome amplification [CA]) centrosome aberrations causing aneuploidy and genomic instability. Compelling data demonstrate that centrosomes are implicated in cancer, because there are important oncogenic and tumor suppressor proteins that are localized in this organelle and drive centrosome aberrations. Centrosome defects have been found in pre-neoplasias and tumors from breast, ovaries, prostate, head and neck, lung, liver, and bladder among many others. Several drugs/compounds against centrosomal proteins have shown promising results. Other drugs have higher toxicity with modest or no benefits, and there are more recently developed agents being tested in clinical trials. All of this emerging evidence suggests that targeting centrosome aberrations may be a future avenue for therapeutic intervention in cancer research. Keywords: centrosomes, cell cycle, mitosis, CA, CIN, cancer therapy